2016
DOI: 10.1016/j.ejvssr.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudoaneurysm of the Deep Palmar Arch After Penetrating Trauma to the Hand: Successful Exclusion by Ultrasound Guided Percutaneous Thrombin Injection

Abstract: IntroductionPseudoaneurysm of the hand is a rare condition; most are treated surgically. Ultrasound guided thrombin injection has not previously been reported as a treatment option for pseudoaneurysms of the deep palmar arch.ReportA man was referred to the emergency department with a swollen, painful hand after penetrating trauma. On physical examination, a pulsating tumor was found on the dorsum of the hand. Imaging revealed a pseudoaneurysm vascularized by the deep palmar arch. Ultrasound guided percutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Regarding the non-autologous bypass option, only one study was reported by Lucchina et al [19] describing the use of an artery graft interposition for the reconstruction of a digital artery PA, which remained patent during the 3-month follow-up period. Although surgical repair is currently considered the gold standard treatment, endovascular techniques such as coil embolization and ultrasound-guided thrombin injection have emerged as promising alternative minimally invasive solutions for treating superficial and deep palmar arch aneurysms [3,10,20]. These techniques are usually indicated in patients with increased surgical hemorrhagic risk and suitable anatomical characteristics of the lesions [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the non-autologous bypass option, only one study was reported by Lucchina et al [19] describing the use of an artery graft interposition for the reconstruction of a digital artery PA, which remained patent during the 3-month follow-up period. Although surgical repair is currently considered the gold standard treatment, endovascular techniques such as coil embolization and ultrasound-guided thrombin injection have emerged as promising alternative minimally invasive solutions for treating superficial and deep palmar arch aneurysms [3,10,20]. These techniques are usually indicated in patients with increased surgical hemorrhagic risk and suitable anatomical characteristics of the lesions [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the deep palmar arch is located underneath, situated about 1.5 cm closer to the carpus, and is formed by the union of the terminal branch of the radial artery and the deep palmar branch of the ulnar artery [ 9 ]. PAs of the palmar area of the hand primarily affect the superficial rather than the deep palmar arch; the latter has been reported only once in the literature [ 10 ]. True aneurysms are usually fusiform in shape and involve all three layers of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of PsA treatment include open surgery, EVT, and thrombin injection. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Peripheral blood flow is often sacrificed during the treatment of PsA in the lower legs because the blood vessels, particularly in the foot, are so narrow that revascularization is difficult while multiple major arteries are present. 1 , 3 Open surgery for PsA after trauma is inexpensive and radical; the compression for surrounding tissue may disappear immediately.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus on exact dose of thrombin for this procedure, the literature describes UGTI to treat both the radial and ulnar arteries. 9,10 One study of 83 pseudoaneurysms demonstrated a relationship between the size of the palmar pseudoaneurysm and the number of thrombin injections required to resolve it. Depending on the size of the palmar pseudoaneurysm, the effective thrombin doses ranged from 200 to 2,500 U.…”
Section: Treatmentmentioning
confidence: 99%